Rethinking private authority : agents and entrepreneurs in global environmental governance - Green, Jessica F. (Princeton University Press, 2014)
"Rethinking Private Authority examines the role of non-state actors in global environmental politics, arguing that a fuller understanding of their role requires a new way of conceptualizing private authority. Jessica Green identifies two distinct forms of private authority--one in which states delegate authority to private actors, and another in which entrepreneurial actors generate their own rules, persuading others to adopt them.Drawing on a wealth of empirical evidence spanning a century of environmental rule making, Green shows how the delegation of authority to private actors has played a small but consistent role in multilateral environmental agreements over the past fifty years, largely in the area of treaty implementation. This contrasts with entrepreneurial authority, where most private environmental rules have been created in the past two decades. Green traces how this dynamic and fast-growing form of private authority is becoming increasingly common in areas ranging from organic food to green building practices to sustainable tourism. She persuasively argues that the configuration of state preferences and the existing institutional landscape are paramount to explaining why private authority emerges and assumes the form that it does. In-depth cases on climate change provide evidence for her arguments.Groundbreaking in scope, Rethinking Private Authority demonstrates that authority in world politics is diffused across multiple levels and diverse actors, and it offers a more complete picture of how private actors are helping to shape our response to today's most pressing environmental problems"--